STUDY OF THE MECHANICAL BEHAVIOR AND DURABILITY OF MORTARS BASED ON PREPARED SAND - Noui , Ammar; Bouglada, Mohammed_Salah; Belagraa, Larbi; Achour, Yacine; Abderazak, Bouzid (Mining science, 2019)
Sand occupies a great proportion of the cementitious matrix product and in particular mortars. Hence, the study of fine aggregates used for concrete and mortar in general, deserves to be objects of research including sand which has always been considered as inert material, whose role is exclusively physical. The study of mortars performances based on prepared sand to assess the effect of the type and rate of substitution of mineral additions pozzolana and blast furnace slag of a natural sand fine fraction (sieve diameter less than 0.16 mm) is seen as the main objective of the present experimental research work. The natural sand replaced size is less than 160 µm and for rheological reasons the maximum replacement rate of natural sand is limited to 10%. The results obtained show a significant improvement of the mechanical properties for the mortars based on the new activated sand. With regard to durability tests of HCl and H2SO4 acids chemical attacks, the substitution of the quartz by active mineral additions in the sand-size skeleton allows an advantageous reduction in loss of resistance up to 50% and a mass gain around 75%.